THE RELATIONSHIP BETWEEN THE ANTHROPOMETRIC MEASURES AND RESPIRATORY FUNCTIONS OF TOBACCO WORKERS - PETER OLAITAN AIYEDUN; SALAMI OLASUNKANMI ISMAILA; DAVID OJO; GIDEON OLABODE ADENIRAN (Journal of Engineering Studies and Research)
The aim of this research was to establish the relationship between some anthropometric measurements and peak expiratory flow rate of tobacco factory workers. Eighty permanent workers who had been employed for at least three years with no history of cardiovascular disease were involved with the study. The measured anthropometric data (chest width and depth, height and weight) were analyzed using SPSS (V 16.0) to develop predictive models for PEFR of tobacco factory workers. It was concluded that the developed models could determine the PEFR of workers in a tobacco manufacturing company.